2015
DOI: 10.1002/2015jc010720
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ocean heat flux on seasonal ice growth in Young Sound (Northeast Greenland)

Abstract: The seasonal ice cover plays an important role in the climate system limiting the exchange of heat and momentum across the air‐water interface. Among other factors, sea ice is sensitive to the ocean heat flux. In this study, we use in situ oceanographic, sea ice, and meteorological data collected during winter 2013/2014 in Young Sound (YS) fjord in Northeast Greenland to estimate the ocean heat flux to the landfast ice cover. During the preceding ice‐free summer, incident solar radiation caused sea surface tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Despite the large number of these artificial returns, some consistent returns between 2.5 and 3.3 m were recorded between late June and mid-July, which correspond with our inferred depths of the platelet layer. Earlier studies using the same model of IMB and underwater sonar demonstrated good agreement between the sounder derived ice thickness and the ice thickness inferred from the temperature string (Kirillov et al, 2015). Therefore, we are confident in the returns other than the artificial returns at 3.8 m depth.…”
Section: Methodssupporting
confidence: 71%
“…Despite the large number of these artificial returns, some consistent returns between 2.5 and 3.3 m were recorded between late June and mid-July, which correspond with our inferred depths of the platelet layer. Earlier studies using the same model of IMB and underwater sonar demonstrated good agreement between the sounder derived ice thickness and the ice thickness inferred from the temperature string (Kirillov et al, 2015). Therefore, we are confident in the returns other than the artificial returns at 3.8 m depth.…”
Section: Methodssupporting
confidence: 71%
“…[], Basedow et al . [], and Marcus and Scheef []. The polynya‐enhanced cell circulation was accompanied by a relative increase in temperature of the subsurface layer (from an average of −1.76°C up to −1.70 f°C) that resulted in the upward heat flux to the ice‐water interface by up to 22–24 W/m 2 at the outer fjord (moorings m02 and m03 ) and up to 14.5 W/m 2 in the inner fjord (mooring m04 ) [ Kirillov et al ., ]. The relatively strong thermal gradient, observed by Dmitrenko et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an ice‐mass balance buoy (IMB) [ Babb et al ., ; Kirillov et al ., ] deployed at the m04 position in October 2013 provided data on ice thickness and snow depth every 30 min until the system was recovered in May 2014 (for more details see Kirillov et al . []).…”
Section: Methodsmentioning
confidence: 99%
“…Then, there is progressive freezing into snow‐ice as latent heat from solidifying ice is expelled from the flooded snow layer through conductive fluxes in the snow above and ice below (Figure d). Assuming that the mass fractions of snow and water in snow‐ice are 2/3 and 1/3, respectively [ Eicken et al ., ; Kirillov et al ., ], the thickness of slush that turns into snow‐ice at each time t can be estimated as htrue(italicttrue)=3(italicFitalicS(t)+Fitalici(t))ρL where F s (t) and F i (t) are the conductive heat flux densities in the snow and in the ice at the flooded layer interface at time t, ρ is the ice density (taken as 900), and L the latent heat of fusion. These conductive flux densities (F = –k dT/dz) are calculated with k ≅ 0.3 W m −1 K −1 at the base of the snow [ Yen , ] and k in the ice as in section 2.3.2. The snow‐ice layer thickness H(t) is then estimated as t0thtrue(italicstrue) ds with the time integration running from the time of the flooding t 0 until time t (Figure d).…”
Section: Evolution Of the Snow And Ice Mass Balancementioning
confidence: 99%